2003
DOI: 10.3818/jrp.5.2.2003.55
|View full text |Cite
|
Sign up to set email alerts
|

Returning Home: Preliminary Findings from a Pilot Study of Soon-to-be-Released Prisoners in Maryland

Abstract: In 2001, researchers at the Urban Institute in Washington, D.C., launched a pilot study in the state of Maryland for a four-state, longitudinal research project examining prisoner reentry. The first stage of the pilot involved self-administered surveys with 324 prisoners in the 30 to 90 days prior to their expected release. These surveys presented many research challenges, including designing a self-administered instrument that would be accessible to the prison population, developing appropriate sampling and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Prior research has indicated that incarceration leads to emotional division in partnerships 9,1113,2427 and can result in partnership dissolution. 11,12,28 To our knowledge, this study is the first to measure the prevalence of the dissolution of relationships at the time of incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has indicated that incarceration leads to emotional division in partnerships 9,1113,2427 and can result in partnership dissolution. 11,12,28 To our knowledge, this study is the first to measure the prevalence of the dissolution of relationships at the time of incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…And after surveying soon-to-be-released inmates in the state of Maryland, Visher and colleagues (2003) found that despite past parole violations and incarcerations, 78% of the 324 inmates (235 males and 89 females) sampled were optimistic about staying out of prison following their release (see also Friestad & Hansen, 2010). It is important to note, however, that Visher et al (2003) did not discuss gender differences and the studies mentioned above did not explore what influences prisoners' outlook regarding postrelease success.…”
Section: Optimism Inmates and Desistancementioning
confidence: 96%
“…The latter issue has been addressed in studies on prisoners’ motivation to change, resettlement, and desistance (Bottoms & Shapland, ; Farrington, ; Maruna, ; Sampson & Laub, , ; Zamble & Quinsey, ). Within this context, prisoners’ own expectations of reoffending are an important but rarely investigated topic (Burnett, ; Dhami, Mandel, Loewenstein, & Ayton, ; Visher, La Vigne, & Castro, ; Zamble & Quinsey, ). Insight to prisoners’ future‐oriented cognitions and their relation to post‐release events and experiences can lead to a better understanding of potential courses of action, during and after imprisonment, which can facilitate or impede desistance from crime.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the challenges that they face, past studies have found that many prisoners are highly optimistic about their lives after release (e.g., Nelson et al, 1999;Visher , La Vigne, & Castro, 2003). On one hand, prisoners' optimism has been linked to positive outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation